2006
DOI: 10.1111/j.1365-2826.2006.01507.x
|View full text |Cite
|
Sign up to set email alerts
|

Altered Expression of SOCS3 in the Hypothalamic Arcuate Nucleus during Seasonal Body Mass Changes in the Field Vole, Microtus agrestis

Abstract: We have previously shown that cold-acclimated (8 degrees C) male field voles (Microtus agrestis) transferred from short day (SD, 8 h light) to long day (LD, 16 h light) photoperiod exhibit an increase in body mass lasting 4 weeks, after which they stabilise at a new plateau approximately 7.5 g (24.8%) higher than animals maintained in SD. By infusing voles with exogenous leptin, we have also demonstrated that SD voles respond to the hormone by reducing body mass and food intake, whereas LD animals increasing b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 84 publications
0
25
1
2
Order By: Relevance
“…In obese humans, except in extremely rare cases, obesity is associated with decreased sensitivity to leptin and increased circulating leptin levels, a phenomenon that has been termed leptin resistance (Frederich et al 1995, Caro et al 1996, Ur et al 1996, Montez et al 2005. Leptin resistance can be either a pathological state, for example, in diet-induced obesity or an adaptive response allowing shifts in body-energy stores, similar to that occurring in seasonal breeders (Rousseau et al 2002, Tups et al 2004, Krol et al 2007, Zieba et al 2008, Scarpace & Zhang 2009, Tups 2009). For example, the Siberian hamster, which has been intensively studied as a model of seasonal mammals, spontaneously reduces its BW by w40% over a 12-week period in winter (Heldmaier et al 1982).…”
Section: Discussionmentioning
confidence: 99%
“…In obese humans, except in extremely rare cases, obesity is associated with decreased sensitivity to leptin and increased circulating leptin levels, a phenomenon that has been termed leptin resistance (Frederich et al 1995, Caro et al 1996, Ur et al 1996, Montez et al 2005. Leptin resistance can be either a pathological state, for example, in diet-induced obesity or an adaptive response allowing shifts in body-energy stores, similar to that occurring in seasonal breeders (Rousseau et al 2002, Tups et al 2004, Krol et al 2007, Zieba et al 2008, Scarpace & Zhang 2009, Tups 2009). For example, the Siberian hamster, which has been intensively studied as a model of seasonal mammals, spontaneously reduces its BW by w40% over a 12-week period in winter (Heldmaier et al 1982).…”
Section: Discussionmentioning
confidence: 99%
“…There are several models of naturally occurring, programmed leptin resistance, including that displayed in seasonal animals (27,28,63) or during pregnancy/lactation (2,21), where increased food consumption and weight gain are necessary to meet the particular biological demands. Additionally, several genetic models of obesity associated with defective or absent leptin receptors reflect a tachyphylaxis to leptin responses (17).…”
Section: Animal Models Of Leptin Resistancementioning
confidence: 99%
“…Studies carried out on field vole (Microtus agrestis), a seasonal animal, provide very interesting information. Field voles, similar to Siberian hamsters, exhibit annual fluctuations in BW during the year and reduction in leptin resistance during LD (Krol et al 2007). This paper raised the very important question of whether the increased level of expression of SOCS-3 is the result or the cause of concomitant weight gain.…”
Section: Experiments I: In Vitro Prl Studymentioning
confidence: 99%
“…This paper raised the very important question of whether the increased level of expression of SOCS-3 is the result or the cause of concomitant weight gain. Furthermore, authors suggested that melatonin, by way of direct or indirect interaction, may be responsible for seasonal changes in the expression of SOCS-3 in the hypothalamus (Krol et al 2007). Since melatonin is the main molecule responsible for signalling the changes in the length of the day, this pineal hormone and/or other hormones that have concentrations in the bloodstream that are highly dependent on the concentration of melatonin (e.g.…”
Section: Experiments I: In Vitro Prl Studymentioning
confidence: 99%